2004
DOI: 10.1159/000081001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serine 392 Phosphorylation in Overexpressed p53 Protein in Human Esophageal Squamous Cell Carcinoma

Abstract: Objective: Posttranscriptional modification involving phosphorylation of wild-type p53 has been considered to play a role in the stabilization of p53. Little is known, however, about the role of phosphorylation of mutant p53 overexpressed in tumors. The aim of this study is to determine the phosphorylation state of p53 in tumors and its contribution to tumor development. Methods: Using immunohistochemical techniques, we examined the phosphorylation of Ser392 and 15 sites in p53 overexpressed in 137 esophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 61 publications
4
29
1
Order By: Relevance
“…Immunohistochemical detection of phosphorylated Ser 392 is more frequent in breast cancers with mutant rather than wild-type p53 (Nenutil et al, 2005). In other tumours the presence of p53 phosphorylated at Ser 392 has been associated with poorer survival (Matsumoto et al, 2004). In this series its presence related to a shorter duration of survival, particularly for those patients receiving adjuvant hormonal therapy.…”
Section: Discussionmentioning
confidence: 55%
“…Immunohistochemical detection of phosphorylated Ser 392 is more frequent in breast cancers with mutant rather than wild-type p53 (Nenutil et al, 2005). In other tumours the presence of p53 phosphorylated at Ser 392 has been associated with poorer survival (Matsumoto et al, 2004). In this series its presence related to a shorter duration of survival, particularly for those patients receiving adjuvant hormonal therapy.…”
Section: Discussionmentioning
confidence: 55%
“…Other authors think that p53 phosphorylated at Ser392 may be considered an independent prognostic factor in advanced human esophageal squamous cell carcinomas (ESCCs). 15 To our knowledge, there are no data in the literature involving an evaluation of p53 protein phosphorylation at Ser20 and Ser392 in ovarian neoplasms.…”
mentioning
confidence: 98%
“…7,13Y17 Only individual results have shown a clinical implication of p53 phosphorylation in human cancer. 15,17 Yap et al 17 suggested that p53-Ser392 phosphorylation may regulate the oncogenic function of mutant forms of p53 protein in breast cancer. Other authors think that p53 phosphorylated at Ser392 may be considered an independent prognostic factor in advanced human esophageal squamous cell carcinomas (ESCCs).…”
mentioning
confidence: 99%
“…Mutated P53 protein was frequently phosphorylated at Ser392 [25]. Matsumoto et al [26] identified a significant correlation between Ser392 phosphorylation P53 and lymphatic invasion for patients with stage II and III advanced ESCC. However, the correlation between increased immunocreactivity and the presence of mutations is somewhat imperfect [27].…”
Section: Discussionmentioning
confidence: 99%